2022
DOI: 10.1111/head.14291
|View full text |Cite
|
Sign up to set email alerts
|

A real‐world, observational study of erenumab for migraine prevention in Canadian patients

Abstract: Objectives To assess real‐world effectiveness, safety, and usage of erenumab in Canadian patients with episodic and chronic migraine with prior ineffective prophylactic treatments. Background In randomized controlled trials, erenumab demonstrated efficacy for migraine prevention in patients with ≤4 prior ineffective prophylactic migraine therapies. The “Migraine prevention with AimoviG: Informative Canadian real‐world study” (MAGIC) assessed real‐world effectiveness of erenumab in Canadian patients with migrai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…Nonetheless, although our findings are overall in agreement with the results reported in the FRIEND study, a direct comparison cannot be done because of significant differences in the number of patients studied (67 vs. 204 in our study) and different medical histories and comorbidities. Moreover, we report similar findings to those recently published for erenumab [19][20][21] and galcanezumab [22,23] in real-world studies in both the EM and CM settings, although again methodological differences exist between studies, including the evaluation of changes in monthly migraine days (MMD) rather than MHD and the definition of the cut-off for treatment response at the level of 30% rather than 50% reduction in MHD. TA B L E 3 Changes in efficacy, disability, and quality of life outcomes at baseline (T0-trimester before initiation of therapy) and after fremanezumab treatment in patients with chronic migraine (n = 107).…”
Section: Discussionsupporting
confidence: 88%
“…Nonetheless, although our findings are overall in agreement with the results reported in the FRIEND study, a direct comparison cannot be done because of significant differences in the number of patients studied (67 vs. 204 in our study) and different medical histories and comorbidities. Moreover, we report similar findings to those recently published for erenumab [19][20][21] and galcanezumab [22,23] in real-world studies in both the EM and CM settings, although again methodological differences exist between studies, including the evaluation of changes in monthly migraine days (MMD) rather than MHD and the definition of the cut-off for treatment response at the level of 30% rather than 50% reduction in MHD. TA B L E 3 Changes in efficacy, disability, and quality of life outcomes at baseline (T0-trimester before initiation of therapy) and after fremanezumab treatment in patients with chronic migraine (n = 107).…”
Section: Discussionsupporting
confidence: 88%
“…In the subsequent 52-week open-label, MMDs decreased by 9.3 from baseline, and the percentage of patients qualifying as 50% responders was 59% [31]. In the real-world setting, the percentage of 50% responders for CM ranged between 34 and 75%, while the reduction in MMDs varied from 9.3 to 12.8, a quite ample heterogeneity that can be explained by differences in study design, duration of follow-up, and inclusion/exclusion criteria [9,10,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…In CM, real-world studies proved a reduction in MMD from 8.2 to 13.9, while the 50% responder rate was between 34 and 75% (4245). Noteworthy, erenumab proved effective in refractory CM patients as well (46).…”
Section: Discussionmentioning
confidence: 98%
“…Real-world studies including EM patients suggested a reduction in MMD between 2.9 to 6.4; the 50% responder rate ranged between 35-76.5% (4244).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation